TOHIR MALIK’S FANTASTIC STORIES: THE POETICS OF PLOT (Лучшие интеллектуальные исследования, 2025)
Abstract; This paper explores the plot poetics in the fantastic stories of renowned Uzbek writer Tohir Malik. Through literary and structural analysis of his short fiction, the study examines how narrative development, symbolic layering, and suspense mechanisms contribute to the artistic depth of his fantastic tales. Malik’s stories are marked by psychological tension, metaphysical speculation, and moral inquiry—all embedded in carefully constructed plots. The research reveals how his narrative architecture serves not only entertainment but also philosophical and didactic purposes.